Effectiveness of solution-focused brief couple therapy in improvement of communication patterns and marital intimacy in women - Elham Abusaidi; Kianoosh Zahrakar; Farshad Mohsenzadeh (Gonabad University of Medical Sciences, 2018)
The aim of current research was to investigate the effectiveness of solution-focused brief therapy in the improvement of communication patterns and marital intimacy among married women. This quasi-experimental research used pretest-posttest design with control group. The statistical population consisted of married women referred to the one of the health houses of Tehran city in 2015. A sample of 24 women was selected according to available sampling method. Based on the obtained score on communication patterns scale and marital intimacy scale the subjects were assigned randomly in two experimental and control groups (12 subjects per group). The experimental group participated in 7 sessions of group solution-focused therapy and the control group received no treatment. The gathered data were analyzed by analysis of covariance. The results show that there were significant differences between the pretest and post-test scores of the experimental group, indicating that the solution-focused brief therapy could significantly improve communication patterns and increase marital intimacy among married women (p>0.05). Thus, interventions based on solution-focused brief therapy could be useful in improving the communication patterns and increasing the marital intimacy.